Financial and governance dilemma at Koperasi Social Finance Malaysia Berhad: an analysis - Siti Noorbani Hussain; Zulkarnain Muhamad Sori; Sazali Abdul Wahab (Penerbit Universiti Malaysia Kelantan, 2019)
The case study approach has been successfully proven as an effective tool in teaching and learning process, particularly at the postgraduate level. Its main function is to understand the real business challenges, business scenarios, and relevant issues faced by the business owners. Therefore, building on a real case study from the cooperative’s industry setting (Koperasi Social Finance Malaysia Berhad), backed by the authors’ own experiences and using “the pseudonyms approach” this book hopes to stimulate the interests and passions in case study writing for the further development of effective learning approaches through case studies among students, academics, and practitioners. Beyond that, this case study will specifically help the readers to understand the processes, contents, and underlying objectives when building a case study; starting from writing case descriptions, implementing case analysis, identifying business problems, identifying strategic issues, and finally to provide recommendations to address the business problems. Indeed, the other main focus of this book is to provide a complete and practical guidance to case study writing for Masters and research students, thus creating a benchmark for both academics and practitioners.